A geochronological and petrological study of anatectic paragneiss and associated granite dykes from the Day Nui Con Voi metamorphic core complex, North Vietnam: constraints on the timing of metamorphism within the Red River shear zone. (25th January 2013) - Palin, R. M.; Searle, M. P.; Waters, D. J.; Parrish, R. R.; Roberts, N. M. W.; Horstwood, M. S. A.; Yeh, M.‐W.; Chung, S.‐L.; Anh, T. T.
Abstract The Red River shear zone (RRSZ) is a major left‐lateral strike‐slip shear zone, containing a ductilely deformed metamorphic core bounded by brittle strike‐slip and normal faults, which stretches for >1000 km from Tibet through Yunnan and North Vietnam to the South China Sea. The RRSZ exposes four high‐grade metamorphic core complexes along its length. Various lithologies from the southernmost core complex, the Day Nui Con Voi (DNCV), North Vietnam, provide new constraints on the tectonic and metamorphic evolution of this region prior to and following the initial India–Asia collision. Analysis of a weakly deformed anatectic paragneiss using P–T pseudosections constructed in the MnO–Na2O–CaO–K2O–FeO–MgO–Al2O3–SiO2–H2O–TiO2–O (MnNCKFMASHTO) system provides prograde, peak and retrograde metamorphic conditions, and in situ U–Th–Pb geochronology of metamorphic monazite yields texturally controlled age constraints. Tertiary metamorphism and deformation, overprinting earlier Triassic metamorphism associated with the Indosinian orogeny and possible Cretaceous metamorphism, are characterized by peak metamorphic conditions of 805 °C and 8.5 kbar between c. 38 and 34 Ma. Exhumation occurred along a steep retrograde P–T path with final melt crystallizing at the solidus at ≥ 5.5 kbar at 790 °C. Further exhumation at 640–700 °C and 4–5 kbar at c. 31 Ma occurred at subsolidus conditions. U–Pb geochronological analysis of monazite from a strongly deformed pre‐kinematic granite dyke from the flank of the DNCV provides further evidence for exhumation at this time. Magmatic grains suggest initial emplacement at 66.0 ± 1.0 Ma prior to the India–Asia collision, whereas grains with metamorphic characteristics indicate later growth at 30.6 ± 0.4 Ma. Monazite grains from a cross‐cutting post‐kinematic dyke within the core of the DNCV antiform provide a minimum age constraint of 25.2 ± 1.4 Ma for the termination of fabric development. A separate and significant episode of monazite growth at c. 83–69 Ma is suggested to be the result of fluid‐assisted recrystallization following the emplacement of magmatic units.